Evaluation of amniotic fluid neutrophil gelatinase-associated lipocalin and L-type fatty acid-binding protein levels during pregnancy - Daisuke Katsura; Shunichiro Tsuji; Shinsuke Tokoro; Ayako Inatomi; Takako Hoshiyama; Nobuyuki Kita; Takashi Murakami (Elsevier, 2024)
Objective: We aimed to examine amniotic fluid neutrophil gelatinase-associated lipocalin (NGAL) and L-type fatty acid-binding protein (L-FABP) levels during pregnancy. Study design: This study included singleton pregnancies. Amniotic fluid samples were collected at the time of vaginal delivery, cesarean section, amniocentesis, amnioreduction, and amnioinfusion. We analyzed changes of the NGAL and L-FABP levels during pregnancy and the factors affecting these values and their association with clinical outcomes. Results: Three hundred and one pregnancies were analyzed. Respective Pearson correlation coefficients for the NGAL and L-FABP levels and gestational age at inspection were − 0.351 and − 0.819 (p <0.001 and p < 0.001, respectively); weak and strong negative correlation were observed. The NGAL level was significantly higher in the intra-amniotic infection group than in the control group (p < 0.001). The L-FABP level was significantly higher in the fetal blood flow abnormalities group than in the control group (p < 0.001). The NGAL and L-FABP levels were significantly higher in the adverse outcomes group than in the control group (p = 0.019 and p < 0.001, respectively), and the respective areas under the concentration-time curve, with optimal cutoff values, for the NGAL and L-FABP levels were 0.693 (14,800 µg/gCr) and 0.864 (378 µg/gCr). Conclusions: Amniotic fluid NGAL and L-FABP levels reflect fetal and neonatal immaturity. Additionally, the NGAL level is a useful predictive factor of intra-amniotic infection, and the L-FABP level is a useful predictive factor of fetal condition and short- and long-term prognoses.